Transformations of youth life in the digital age: work, knowledge and subaltern identities - González Estrada, Yuleidys; Rosique Cárdenas, Iramis; Manzano Castillo, Yohandry (Multidisciplinar (Montevideo), 2025)
Introduction: The study examined the influence of digital technologies on the configuration of subjectivity and youth identities in Cuba. It started from the concept of “technologically encoded sociality” to analyze how digital capitalism transformed the perception of success and autonomy in youth. It addressed the relationship between the labor market, access to information, and the processes of domination/emancipation of subaltern identities.Development: The analysis included three main areas: the impact of digitization on youth employment, the circulation of knowledge and the transformation of subordinate identities. It became clear that young people faced job insecurity, despite the growth of digital opportunities. In terms of access to information, interaction on social networks and digital platforms changed the way young people consumed and generated knowledge, promoting new learning dynamics. The study also highlighted that self-help and entrepreneurship content influenced the perception of success, prioritizing economic growth and self-sufficiency over emotional stability.Conclusion: It was concluded that digital technologies reconfigured youth identity in Cuba, establishing new dynamics in the workplace, socially and affectively. However, it was noted that digitization did not operate neutrally, but was permeated by market logic, affecting the aspirations and behaviors of young people.